Sinergi Tripusat Pendidikan sebagai Strategi Penguatan Karakter Ketaatan dan Kewarganegaraan di Era Disrupsi Digital - Maharatu, Andi Puan; Marzuki, Marzuki (Journal of Moral and Civic Education, 2026)
Moral degradation and disobedience to rules in the era of digital disruption are the urgency of this article. This article aims to analyze the synergy mechanisms between families, schools, and communities in strengthening values ​​education. Using a qualitative-analytical literature study method, this study examines literature related to Bronfenbrenner's Ecological Theory and Joyce Epstein's partnership model. The findings indicate that building internal compliance requires coherence between the family's authoritative parenting style, the school's hidden curriculum, and community social capital. This study concludes that revitalizing the Tripartite Education concept through collaboration is necessary to address value dissonance in students. However, the study's limitations lie in the obstacles to generalizing implementation due to parents' lack of digital literacy and teachers' pedagogical readiness. Therefore, strengthening stakeholder capacity and transforming schools as integrators of the character education ecosystem is necessary.